Diversity and Distribution of True Bugs (Heteroptera) in Ahilyanagar, Maharashtra, India: A Preliminary Study - Sukhdeo, Pande Gajanan; Shahid, Inamdar Nagma (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Heteropterans are well-known as true bugs and are notorious crop pests. Ahilyanagar, the largest district of Maharashtra, encompasses diverse habitats conducive to a rich heteropteran fauna. This study presents preliminary insights into the diversity of heteropteran fauna across selected sites within Ahilyanagar. Specimens were collected, preserved, and taxonomically analysed, revealing 61 taxa representing 49 genera and 12 families. Pentatomidae emerged as the most diverse family, with 17 taxa, followed by Coreidae, Reduviidae, Dinidoridae, Pyrrhocoridae, Lygaeidae, Miridae, Scutelleridae, and Alydidae. This research constitutes the first comprehensive report on Heteroptera from Ahilyanagar, including new distributional records that enrich Maharashtra's faunal resources and inform pest management strategies.